UKURAN LAHIR, KERAGAAN STATUS GIZI, DAN KOMPOSISI TUBUH MAHASISWA TPB-IPB - Pertiwi, Restu; Rimbawan, Rimbawan (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to analyze the correlation between size at birth, nutritional status profile, and body composition of the first year students entering Bogor Agricultural University at 2013. Design of this study was cross-sectional with purposive sampling. The study was carried out with 45 males and 65 females. Result showed that most of students had normal size at birth. There was no significant difference between male and female in size at birth. A number of 66.1% subjects had normal nutritional status and most of them had normal body composition. Percent body fat, visceral fat, fat free mass, and waist-to-hip ratio were significantly different between male and female subjects. Birth weight was significantly correlated with body mass index (p=0.023), whereas birth length had significant correlation with fat free mass (p=0.040).